Hubungan Self-Efficacy Dengan Stres Akademik Mahasiswa Keperawatan S1 Tingkat I Reguler Fitkes Unjani Cimahi - MUSRI; sulthonul Hakim, Rizki; ismafiaty (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Background: New students don't know much about campus. They seek relationships, develop themselves and become independent. The new atmosphere of lectures can make students experience academic stress, if students' high self-efficacy can manage academic stress. Objective: to determine the relationship between self-efficacy and academic stress in Regular Fitkes Unjani Undergraduate Nursing Students Level I. The research method used is a cross sectional design. Method: Using descriptive analysis (Univariate) and correlation test using Chi-Square. The overall population of Unjani Health Fitkes Regular Level I Undergraduate Nursing Students was 188 people, the sampling technique was proportionate stratified random sampling and simple random sampling totaling 66 respondents. The instruments used were the General Self-efficacy Scale (GSES) and the Student Academic Stress Scale (SASS). Results: it was found that the majority (57.6%) of respondents had high academic stress as many as 38 respondents and the majority (54.5%) of respondents had high self-efficacy as many as 36 respondents. There is a relationship between self-efficacy and academic stress for undergraduate nursing students at Level I Regular Fitkes Unjani (PValue = 0.034 <0.05). Conclusion: There is a relationship between self-efficacy and academic stress for undergraduate nursing students at Level I Regular Fitkes Unjani. Suggestion: It is recommended that students pay more attention to their body condition if they are stressed and can manage stress, which can also increase self-efficacy and do as students do, read the RPS and understand everything about the major the student is taking.